2012
DOI: 10.1063/1.3677659
|View full text |Cite
|
Sign up to set email alerts
|

Quasiparticle relaxation across the multiple superconducting gaps in the electron-doped BaFe1.85Co0.15As2

Abstract: We study the quasiparticle relaxation dynamics in the electron-doped superconductor, BaFe1.85Co0.15As2 (BFCA) by using optical spectroscopy in both time and frequency domains. The estimate of the electron−phonon (el–ph) coupling constant from quasiparticle relaxation rate in time domain gives a value of ∼0.16 that is much too small to give a TC of 25 K. We obtain a negative value of the Coulomb pseudopotential that implies that the el−ph interaction alone is not strong enough to induce a superconducting transi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…To avoid systematic discrepancies due to different experimental methods, we mainly summarize experimental 𝜆 𝐴1g values obtained by using time-resolved ultrafast optical spectroscopy (including time-resolved angle-resolved photoemission spectroscopy, red spheres and squares), [5,6,8,9,53] as well as theoretical results (blue spheres and squares). [35,37,39,42,43,46,48] Note that some of the data are retrieved by the authors (see the Supplementary Material).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…To avoid systematic discrepancies due to different experimental methods, we mainly summarize experimental 𝜆 𝐴1g values obtained by using time-resolved ultrafast optical spectroscopy (including time-resolved angle-resolved photoemission spectroscopy, red spheres and squares), [5,6,8,9,53] as well as theoretical results (blue spheres and squares). [35,37,39,42,43,46,48] Note that some of the data are retrieved by the authors (see the Supplementary Material).…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, we perform ultrafast optical spectroscopy experiments on Fe 1.05 Se 0.2 Te 0.8 (𝑇 c = 10 K) and Fe 1.01 Se 0.2 Te 0.8 (𝑇 c = 13.5 K) single crystals, and obtain the 𝜆 𝐴1g values to be 0.11 and 0.13, respectively (see the Supplementary Material). [5,6,8,9,53]). Blue sphere (squares): retrieved theoretical calculation results of FeSe (FeAs)-based superconductors.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Usually the anomalous T dependence of τ exp is observed in many gapped systems, for example, phaseordered systems showing an energy gap opening in the electron band below the transition temperature T c . It has been found that a wide variety of superconductors [1][2][3][4][5][6][7][8][9][10][11][12][13] and density-wave compounds [14][15][16][17][18][19] show diverging behavior of τ exp near T c , as confirmed by femtosecond time-resolved optical spectroscopy. 1,4,5,[7][8][9][10][11][12][13][14][15][16][17]19 The divergence of τ exp in these gapped systems is believed to result from a recursive energy transfer between electrons and phonons.…”
Section: Introductionmentioning
confidence: 91%